2015
DOI: 10.1111/hpb.12322
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the International Study Group for Liver Surgery definition of bile leak after a liver resection and the role of routine operative drainage: an international multicentre study

Abstract: The ISGLS definition of bile leak after liver surgery appears robust and intra-operative drain usage did not prevent the need for subsequent drain placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
91
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 17 publications
(24 reference statements)
12
91
1
4
Order By: Relevance
“…level 1b evidence, 1 study [13] was grade level 2b evidence, and the remaining studies [5,12,[25][26][27] were cohort studies of grade 4 evidence. No ongoing studies could be identified in clinical trial registers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…level 1b evidence, 1 study [13] was grade level 2b evidence, and the remaining studies [5,12,[25][26][27] were cohort studies of grade 4 evidence. No ongoing studies could be identified in clinical trial registers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Incisional and organ/space SSIs were diagnosed by the surgeon who performed the postoperative follow-up. Postoperative bile leakage was defined as the identification of macroscopic bile discharge or as the presence of bilirubin concentrations in the drainage fluid 3 times greater than those in the serum after 3 postoperative days [13]. Retrograde drain infection was defined as organ/space SSI without bile leakage or evidence of bacterial infection in the initial drainage fluid culture.…”
Section: Postoperative Carementioning
confidence: 99%
“…29 Because of the heterogeneity of definitions in the literature, the true incidence of bile leak complications is difficult to assess. 30 With regard to long-term health problems, most of our patients had minor complaints (eg, minor scar problems). These findings are in line with the present literature.…”
Section: Discussionmentioning
confidence: 91%